Efektivitas Larvasida Granul Ekstrak Etanol Daun Pisang Nangka (Musa x paradisiaca L.) terhadap Larva Nyamuk Aedes aegypti - Anna Yuliana; Rusdi Aris Rinaldi; Nur Rahayuningsih; Firman Gustaman (ASPIRATOR - Journal of Vector-borne Disease Studies, 2021)
Musa x paradisiaca L. leaves are known to contain phenols, flavonoids, saponins, tannins, and other compounds that can be used as larvicides. This study aims to determine the effect of Musa x paradisiaca L leaves’ ethanol extract granules on the mortality of Aedes aegypti larvae. The Research was experimental in two stages of effectiveness testing, that are extract and granule formula effectiveness test. Data were analyzed using the Kruskal-Wallis test and the Mann-Whitney test. The extraction method used was maceration using 96% ethanol. The concentration of the extract dosage used were 0.2; 0.5; 1; 2; and 4%, with control (+) temephos and control (-). Repetitions were carried out 3 times with a sample total of 675 larvae. Observations were made for 12 and 24 hours. Preparation of granules using 2 formulas, formula 1 granules without extract and formula 2 granules with the extract. To fulfill the granule formulation criteria, the preparation was evaluated. The results showed that the concentration of 4% extract was the most effective at 98.7%, as stated by the Kruskal-Wallis test result,p-value <0.05, which means that there was an effect on the effectiveness of larvicide. The percentage of mortality of larvae given formula 2 is 100% and based on the Mann-Whitney test with value p<0.05, there is a difference between granule 1 and 2 formula. Criteria of granule including moisture content (1.72 %), angle of rest 240, flow velocity (50 gr/sec), and dispersion time (2.25 minutes). The granular formula of Musa x paradisiaca L leaves can make the application easier and hopefully can be used as effectively as synthetic larvicide in the community.